Antileishmanial IgG and IgE antibodies recognize predominantly carbohydrate epitopes of glycosylated antigens in visceral leishmaniasis - Atta,AM (2004)
The specificity of human antileishmanial IgG and IgE antibodies to glycosylated antigens of Leishmania chagasi was evaluated. An ELISA was performed with soluble leishmanial antigen (SLA) and a panel of 95 sera including samples from patients with subclinical infection (SC) and visceral leishmaniasis (VL), subjects cured of visceral leishmaniasis (CVL), and from healthy individuals from endemic areas (HIEA). Antileishmanial IgG were verified for 18 (40%) of 45 SC subjects (mean absorbance of 0.49 ± 0.17). All nine sera from VL patients had such antibody (0.99 ± 0.21), while 11 (65%) of 17 CVL individuals were seropositive (0.46 ± 0.05). Only three (12%) of 24 HIEA controls reacted in IgG-ELISA. Antileishmanial IgE was detected in 26 (58%) of 45 SC patients (0.35 ± 0.14), and in all VL patients (0.65 ± 0.29). These antibodies were also detected in 13(76%) of 17 CVL subjects (0.42 ± 0.14) while all HIEA controls were seronegative. There was no correlation between antileishmanial IgG and IgE antibody absorbances. Mild periodate oxidation at acid pH of SLA carbohydrates drastically diminished its antigenicity in both IgG and IgE-ELISA, affecting mainly the antigens of 125, 102, 94, and 63 kDa as demonstrated by western immunoblotting.